1993
DOI: 10.1161/01.str.24.2.320
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality of life in stroke.

Abstract: Background and Purpose: Little attention has been focused on quality of life in stroke outcome research. The purpose of this review is to outline the meaning of the concept, describe important methodological issues and methods of assessment, review existing quality of life measures, and discuss criteria for selecting an appropriate instrument.Summary ofReview:The following 10 quality of life instruments were reviewed: COOP Charts; Euroqol; Frenchay Activities Index; Karnofsky Performance Status Scale; McMaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0
14

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(164 citation statements)
references
References 55 publications
4
145
0
14
Order By: Relevance
“…While the ASIA scale does not measure spasticity, coordination or gait-it is useful as a metric to register subtle changes in sensory and motor function. The Karnofsky Index was designed as a functional index for cancer patients, but has also been used in other areas as a reliable means of assessing function [9]. The Brainstem Disability Index [5] used in this report is not validated, but is used by the authors to measure improvement in the panoply of symptoms generally attributed to neurological dysfunction of the brainstem based upon the encyclopedic descriptions of others [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…While the ASIA scale does not measure spasticity, coordination or gait-it is useful as a metric to register subtle changes in sensory and motor function. The Karnofsky Index was designed as a functional index for cancer patients, but has also been used in other areas as a reliable means of assessing function [9]. The Brainstem Disability Index [5] used in this report is not validated, but is used by the authors to measure improvement in the panoply of symptoms generally attributed to neurological dysfunction of the brainstem based upon the encyclopedic descriptions of others [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…This review is guided by Wilson and Cleary HRQOL model [25] and the HRQOL dimensions reported in de Haan, et al [24].…”
Section: The Hrqol Of Stroke Survivors In Africamentioning
confidence: 99%
“…The psychological health includes emotional status and cognitive functioning [24]. Presence of emotional symptoms such as anxiety [30] or Depression adversely affects HRQOL [30,31,32,33,34,35] more than the impairment of physical function [33] because depression negatively influence physical function [34].…”
Section: Psychological Healthmentioning
confidence: 99%
See 2 more Smart Citations